2021
DOI: 10.1080/10438599.2020.1859751
|View full text |Cite
|
Sign up to set email alerts
|

Economic complexity and jobs: an empirical analysis

Abstract: This paper analyses the impact of economic complexity on the labour market using annual data on OECD countries for the period 1985-2008 and averaged data over the period 1990-2010 for 70 developed and developing countries with a large number of controls. We show that moving to higher levels of economic sophistication of exported goods leads to less unemployment and more employment, revealing that economic complexity does not induce job loss. Our findings remain robust across alternative econometric specificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 87 publications
2
33
0
1
Order By: Relevance
“…FDI contributes to economic growth only when a sufficient absorptive capability of advanced technologies is available in the host economy. Economic development should align with the fundamental structure of capital and labour [ 21 ]. It must adhere to the economy's competitive advantage to accomplish long-term accumulation and constant upgrading of the industrial design to create sustainable economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…FDI contributes to economic growth only when a sufficient absorptive capability of advanced technologies is available in the host economy. Economic development should align with the fundamental structure of capital and labour [ 21 ]. It must adhere to the economy's competitive advantage to accomplish long-term accumulation and constant upgrading of the industrial design to create sustainable economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of studies have examined the nexus between economic complexity and different economic variables, basically to understand national structural transformations process through product sophistications and export activities for national development (Du and O’Connor, 2019; Saadi, 2020; Adam et al , 2021). They suggest that economic complexity has important implications for national entrepreneurial development (Du and O’Connor, 2019; Nguyen et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Adam, et al. (2021) found that economic complexity affects unemployment rates in developed countries and argued that people in a less complex economy face more limited employment opportunities. In contrast, living in a complex economy combined with the growth of high‐tech products provides more employment opportunities for people in the community, allows for higher income levels and reduces inequality in the distribution of income.…”
Section: Theoretical Backgroundmentioning
confidence: 99%